Colon Cancer Cell Secretes EGF to Promote M2 Polarization of TAM Through EGFR/PI3K/AKT/mTOR Pathway. (19th July 2019) - Lian, Guanghui; Chen, Shuijiao; Ouyang, Miao; Li, Fujun; Chen, Linlin; Yang, Junwen
Background: Tumor environment has been recognized to affect cancer cell progression, such as tumor-associated macrophages. However, increasing evidences suggest that tumor cells are capable of regulating polarization of tumor-associated macrophages. In this study, we investigate the mechanism of how colon cancer cell impacts tumor-associated macrophages polarization. Methods: We employed flow cytometry to detect marker molecules on macrophage membrane, such as CD68, CD16, and CD204. In addition, we used enzyme-linked immunosorbent assay to examine the level of these cytokines (interleukin-6, interleukin-1β, interleukin-10, and Arginase-1) secreted by colon cancer cells into the culture medium. Western blot was utilized to probe downstream proteins of epidermal growth factor receptor (EGFR)/phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway. Results: We cocultured colon cancer cell lines (HCT8 or HCT116) with human myeloid leukemia mononuclear cells (THP-1) and found that interleukin-6 and interleukin-1β levels were reduced, and instead, interleukin-10 and Arginase-1 levels were elevated, suggesting that colon cancer cells contributed to M2 polarization of THP-1. Meanwhile, high level of various growth factors (transforming growth factor-β [TGF-β], epidermal growth factor [EGF], and hepatocyte growth factor [HGF]) was observed in the medium of THP-1 cocultured with colon cancer cells. Furthermore, the protein level of phosphorylated PI3K, AKT, and mTOR significantly increased in THP-1 cell cocultured with colon cancer cells compared to THP-1 group. Besides, we established that colon cancer cells exerted their stimulatory effect on M2 polarization of macrophage from monocyte THP-1 using EGFR antibody mAb225 and PI3K inhibitor LY294002. Conclusion: We provide evidence that EGF which are secreted by colon cancer cells play contributory role in M2 polarization of macrophages, which support the notion that tumor environment, including tumor-associated macrophages, can be targeted to develop effective strategies for treating cancer.